Impact of amiodarone and cisapride on simulated human ventricular electrophysiology and electrocardiograms - Wilhelms, Mathias; Scholz, Eberhard P. (Europace, 2012)
AbstractAims. Amiodarone and cisapride are both known to prolong the QT interval, yet the two drugs have different effects on arrhythmia. Cisapride can cause t